WIPO Mediation, arbitration, expedited arbitration and expert determination rules and clauses (WIPO publication, 2020)
This publication contains the rules of the dispute resolution procedures administered by the WIPO Arbitration and Mediation Center, namely the WIPO Mediation Rules, the WIPO Arbitration Rules, the WIPO Expedited Arbitration Rules WIPO, and the WIPO Expert Determination Rules. Esta publicación contiene los reglamentos de los procedimientos de solución de controversias administrados por el Centro de Arbitraje y Mediación de la OMPI, a saber, el Reglamento de Mediación de la OMPI, el Reglamento de Arbitraje de la OMPI, el Reglamento de Arbitraje Acelerado de la OMPI, y el Reglamento de Decisión de Experto de la OMPI.